Right Prefrontal Cortex and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The relation between MRI anatomical measures of specific frontostriatal structures (prefrontal cortex and basal ganglia) and response inhibition deficits observed in attention deficit hyperactivity disorder (ADHD) was studied at the Western Psychiatric Institute and Clinic, University of Pittsburgh, PA; and the National Institute of Mental Health, Rockville, MD.